2020
DOI: 10.3390/ani10020242
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of an Unmedicated Feeding Program Aimed to Reduce the Use of Antimicrobials in Nursery Piglets: Impact on Performance and Fecal Microbiota

Abstract: This study aimed to assess the impact of two different feeding programs, including or not antimicrobials, on gut microbiota development at early ages in commercial pigs. For this, 21-day-old weaned piglets were distributed into 12 pens (6 replicates with 26 pigs each) and fed ad libitum until fattening with: standard commercial formula with antibiotics and zinc oxide (2400 ppm) (AB), and alternative unmedicated feed formula (UN). Subsequently, the animals were moved to the fattening unit (F) receiving a common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
3
3
0
1
Order By: Relevance
“…In agreement with these findings, faecal and intestinal microbial diversity was also reduced when PW diets were supplemented with pharmacological levels of ZnO, alone or in combination with antibiotics in previous studies 46 48 , although sometimes it was unaffected 35 , 49 , 50 . Conversely, it has also been reported that high doses of ZnO can even increase α-diversity index values 51 , 52 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In agreement with these findings, faecal and intestinal microbial diversity was also reduced when PW diets were supplemented with pharmacological levels of ZnO, alone or in combination with antibiotics in previous studies 46 48 , although sometimes it was unaffected 35 , 49 , 50 . Conversely, it has also been reported that high doses of ZnO can even increase α-diversity index values 51 , 52 .…”
Section: Discussionsupporting
confidence: 87%
“…Lactobacillus spp. were also reduced in rectal samples in another study when ZnO was administered PW 50 , but conversely, a study by López-Colom et al 49 reported an increase in Lactobacillus spp. relative abundance in the faeces when ZnO was administered in combination with antibiotics for 9 days PW.…”
Section: Discussionmentioning
confidence: 83%
“…The mRNA expression levels of HSP27 in the livers were remarkably decreased in pigs fed P-Zn, ZnArg1, ZnArg2, and ZnArg3 diets compared with the Con treatment. The positive correlation between HSP expression and stress was previously reported in other studies [2,4,13]. The low gene expression of HSP27 in the liver and a tendency for lower blood cortisol in the ZnArg2 and ZnArg3 treatments may indicate a lower stress level compared with the Con treatment.…”
Section: Discussionsupporting
confidence: 80%
“…The health condition of piglets is highly unstable at weaning because of the stress of changing feed form, separation from the mother sow, and changes in the physical environment [1][2][3]. These stressors may cause dysbiosis due to sudden microbial changes in the intestine [1,4]. Postweaning intestinal microbiota dysbiosis is associated with some unstable situations including enteric infectious pathogens growth, leaky gut, and incomplete intestinal integrity [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation